ANALISIS POTENSI EKONOMI KOTA GORONTALO DENGAN PENDEKATAN MODEL BASIS EKONOMI - Joice Machmud; Umar Sako Baderan; Iswan L. Lasena (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2019)
This study aims to: 1) Identify which sector is the base sector in Gorontalo City from 2014 to 2018, and 2) Identify the position of economic sectors in Gorontalo City from 2014 to 2018. The research method uses a quantitative approach with quantitative descriptive research type. The results obtained: 1) Based on the LQ analysis of GRDP in Gorontalo City for the period 2014-2018, it is known that there are 15 sectors which are the base sector or LQ˃1, namely the largest contribution in Gorontalo City is contributed by the wholesale and retail trade sector; car repair and recycling with a value of 14.92%. Meanwhile, the lowest sector contribution came from the electricity and gas procurement sector at 0.05%. 2) The results of the Klassen typology analysis showed that sectors belonging to Quadrant I or the criteria for advanced and rapidly growing sectors were found in twelve sectors. Meanwhile, in Quadrant II, the criteria for advanced but depressed sectors are two sectors. In Quadrant III or criteria for potential or still developing sectors, there are two sectors. Whereas in Quadrant IV or relatively underdeveloped sectors, there are no sectors that fall into this category, and 3) Based on the results of the classification typology analysis, Gorontalo City is in the position of Quadrant I, which has a sector that is advanced and growing rapidly.Keywords: Economic Potential, Economic Basis